Factors Driving the Adoption of Fintech Services: An Empirical Analysis of Customers of Commercial Banks in Kathmandu - Bhujel, Sujan (Apex Journal of Business and Management, 2024)
This study aims to empirically explore the influences of customer trust (CT), data security (DAS), perceived usefulness (PU), and perceived ease of use (PPEU) on commercial bank customers' intentions to adopt fintech services in Kathmandu Valley. The study is based on the technology acceptance model (TAM). The data were collected through structured response with 390 sample size from Kathmandu. The descriptive and correlational research design was used for the study. Multiple regression modelling was employed to ascertain the effect of identified variables on fintech service adoption. The correlation analysis results revealed a positive relationship between CT, DAS, PU, PEU, FP, and Fintech Service Adoption (FSA). The regression analysis results indicated that data security, perceived usefulness, and fintech service promotion have a significant effect on customers' intentions to adopt fintech services. On the contrary, the effect of customer trust and perceived ease of use was found to be insignificant on fintech service adoption. The fintech service providers should consider robust data security protections, comprehensive communication regarding data protection processes, and the greater usefulness of fintech products and services, ultimately increasing customer confidence to adopt the different fintech services.